ANALISIS PERHITUNGAN PENCATATAN DAN PELAPORAN PAJAK PERTAMBAHAN NILAI ATAS EKSPEDISI ANTAR PULAU PADA PT. TAJUR JAKARTA - Rundengan, Priscilia Joanna; Tinangon, Jantje; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Value-added tax represent the source of revenue for very dominant state,to fulfill requirement of people. CompanyÂ  as a taxpayer have to carry out their tax liability in accordance with the provisions of the tax laws are dynamic and constantly changing according to the rate of development of countryâ€™s economics. PT. Tajur Jakarta was established in 1967 which is located in Jl. Jati Baru No. 83 where the main activities of company is a shipping that uses trucking services, and that companies that count, reecord, and report Value Added Tax on the consumers of services on goods subject to Value Added Tax.The method in this research is using descriptive analysis which is describe the case studies and literature. Case studies conducted in PT TAJUR Jakarta while literature conducted by collecting data from the literature relevant to the Value-added tax. Pursuant to result of obtained research from the study,the company calculating, recording and reporting properly and in accordance with the Law No. 42 of 2009,using the rate of 10% for each taxable service / goods taxable, and also the results obtained also that the company has to deposit and tax reporting using e-SPT return and paid through the bank by the 15th of each month after the end of the tax period in accordance with law No. 42 of 2009 on Value Added Tax.